Cheese perception in the North American market: empirical evidence for domestic vs. imported parmesan. Issue 7 (4th July 2016) - Boatto, Vasco; Rossetto, Luca; Bordignon, Paolo; Arboretti, Rosa; Salmaso, Luigi
Abstract : Purpose: The paper is aimed to detect market segments where consumers have a different knowledge of domestic and imported Parmesan cheese in US and Canada. The results may be helpful in understanding to what extend North America consumers appreciate Parmesan cheese and brands, Parmesan consumption and price while recognizing market segments according to consumer awareness, involvement and covariate effects. Design/methodology/approach: A class of mixture models, known as CUB (Combination Uniform Binomial), is applied to survey data collected in US and Canada. A questionnaire, filled out by 540 restaurant customers, collects opinions about consumption, purchase features and price. The CUB model estimates the two latent variables, known as feeling and uncertainty, explaining the respondent's behavior as awareness and involvement variability while the CUB clustering procedure detects market segments. Findings: CUB results show that the Parmesan is a well-known cheese but also that a small share of consumers look for the place of origin. The model detects market segments where consumers express better awareness on taste, price and origin while the knowledge of imported Parmesan brands is lacking. Most of consumers, not paying attention to the origin, would hardly switch to the imported Parmesan because of higher price or because they are already satisfied of the domestic cheese. Research limitations/implications: The results suffer some restrictions in the sample representativeness. A further analysis, where the survey is done at retail and advances in CUB models, may improve the market segmentation procedure allowing a better generalization of results. Practical implications: The survey results highlights the appreciation and consumption of Parmesan cheese, especially for its taste, as well as a low perception of Italian brands. Consequently, trade companies should focused their communication strategy on activities encouraging North American consumers to taste Italian Parmesan brands (eg. tasting sessions, price promotions) instead of costly and less effective advertising campaigns. Originality/value: The CUB model is an innovative and flexible no parametric approach for evaluating consumer behavior and for segmenting the market while dealing with complex problems of food knowledge.